Intravenous anesthetic propofol suppresses leukotriene production in murine dendritic cells. (September 2013) - Inada, Takefumi; Ueshima, Hironobu; Shingu, Koh
<x xml:space="preserve">Abstract</x> Leukotrienes, divided into cysteinyl leukotrienes (CysLTs), which are important mediators of asthmatic responses, and leukotriene B4 (LTB4), a chemotactic and chemokinetic agent for leukocytes, are potent lipid mediators generated from arachidonic acid by 5-lipoxygenase (5-LO). Leukotrienes are also considered to have immunoregulatory and pro-inflammatory actions. Propofol is an intravenous anesthetic widely used for anesthesia and sedation that is alleged to possess anti-inflammatory properties. The present study examined the effect of propofol on leukotriene production by dendritic cells (DC). In murine bone marrow-derived DC, propofol significantly suppressed CysLT and LTB4 production after short-term stimulation with zymosan. The protein levels of cytosolic phospholipase A2 and 5-LO, or arachidonic acid release from plasma membranes, were not affected by the presence of propofol. Although zymosan treatment induced or enhanced the phosphorylation of ERK1/2, p-38 MAPK, and JNK, which presumably up-regulates the activity of 5-LO, the presence of propofol had no additional effect on the phosphorylation status of any of these MAPKs. Similarly, zymosan significantly increased the concentration of intracellular calcium, which is the most crucial activator of 5-LO, but no additional concentration changes were observed with the addition of propofol. Lastly, in an in-vitro cell-free ferrous oxidation-xylenol orange assay, propofol significantly inhibited the 5-LO activity of purified human recombinant 5-LO enzyme with an IC50 of ~7.5 µM. Thus, propofol's inhibition of 5-LO is not likely restricted to the circumstances surrounding the production of leukotrienes from DC, but applicable to other types of immune and non-immune cells that produce leukotrienes. The 5-LO-inhibiting activity of propofol may, at least in part, contribute to the well-known anti-inflammatory activity of propofol.